Maintenance therapy in non-small cell lung cancer. Issue 7 (July 2015) - Genestreti, Giovenzio; Di Battista, Monica; Cavallo, Giovanna; Bartolotti, Marco; Brandes, Alba A
<x xml:space="preserve">Abstract</x> Several randomized trials have investigated the role of maintenance treatment for patients with advanced non-small cell lung cancer (NSCLC) not progressed after completion of first-line chemotherapy, with good performance score (PS) and no persistent chemotherapy-induced toxicity. Two separate strategies have been developed: the immediate use of non-cross-resistant drug (switch maintenance or early second-line therapy) or the continuation of platinum partner alone (continuation maintenance) or in combination with other drug (combination maintenance). Here we discuss how the benefits demonstrated in these studies may change clinical practice (in terms of potential toxicity and costs) and reflect on factors that may identify subgroups of patients who might benefit from maintenance therapy in general, and which maintenance therapy specifically.